Prevalence of polycystic ovary syndrome in a metabolically healthy obese population. Issue 2 (2nd May 2019) - Mu, Liangshan; Zhao, Yue; Li, Rong; Lai, Yuchen; Chang, Hsun‐Ming; Qiao, Jie
Abstract: Objective: To determine whether polycystic ovary syndrome (PCOS) prevalence is increased among metabolically healthy obese (MHO) women. Methods: A national epidemiologic survey in 10 provinces and municipalities of China between October 2007 and September 2011. Women were stratified into four groups according to metabolic health (assessment by Adult Treatment Panel III) and obesity (body mass index [BMI] ≥28): metabolically healthy nonobese (MHNO), metabolically unhealthy nonobese (MUNO), MHO, and metabolically unhealthy obese (MUO). PCOS was diagnosed via Rotterdam Criteria. Participants completed a questionnaire and underwent physical and transvaginal ultrasound examination. BMI, blood pressure, glucose, and lipid profile were measured. Results: The survey included 3551 women. The MHO group had a higher prevalence of PCOS and chronic anovulation versus nonobese groups (all P <0.05). Obesity was a risk factor for PCOS (odds ratio [OR], 2.30; 95% confidence interval [CI], 1.68–3.14, P <0.05). Being metabolically unhealthy was a risk factor for PCOS (OR, 1.32; 95% CI, 1.09–1.60; P <0.05). The MHO group had an increased risk of PCOS relative to the MHNO group (OR, 2.39; 95% CI, 1.42–4.02; P <0.05). Conclusion: MHO women had an increased risk of PCOS and chronic anovulation. Obesity might be an independent risk factor for these two disorders. Abstract : Metabolically healthy obese women had a substantially increased risk of polycystic ovary syndrome and chronic anovulation as compared with nonobese women in a large population.